Topical collection : hydrogeology of a cold-region watershed near Umiujaq (Nunavik, Canada) - Ouellet, Michel; Therrien, René; Lemieux, Jean-Michel; Fortier, Richard; Molson, John W. H. (Hydrogeology Journal, 2020)
A cold-region watershed located in the discontinuous permafrost zone near Umiujaq (Nunavik, Canada) was studied in order to increase understanding of the subarctic water cycle and permafrost dynamics. This essay gives an overview of the research, summarised in a collection of six papers that: respectively characterize the physical three-dimensional cryo-hydrogeological system, present a detailed water balance of the watershed, characterize groundwater and surface-water hydrogeochemistry, describe the application of a tracer method to determine groundwater fluxes, develop a two-dimensional numerical model identifying impacts of groundwater flow on permafrost dynamics, and present a parameter sensitivity analysis. The work serves as a guide for developing site characterization plans at similar permafrost-impacted sites and for evaluating their groundwater resource potential. Un petit bassin versant situé dans la zone de pergélisol discontinu près d’Umiujaq (Nunavik, Canada) a été étudié afin de mieux comprendre le cycle de l’eau et améliorer les connaissances sur la dynamique du pergélisol dans un environnement subarctique. Cet essai présente le contexte dans lequel les articles contenus dans ce recueil thématique de six articles ont été réalisés, ainsi qu’un bref aperçu de leur contenu. Les articles abordent respectivement les thèmes suivants: la modélisation géologique 3D du système aquifère, la réalisation d’un bilan hydrique détaillé du bassin versant, la caractérisation hydrogéochimique des eaux souterraines et des eaux de surface, l’application d’une méthode de traçage pour quantifier les flux d’eau souterraine, la réalisation d’un modèle numérique 2D identifiant les impacts de l’écoulement des eaux souterraines sur la dynamique du pergélisol et présente une analyse de sensibilité des paramètres du modèle. Les travaux présentés pourront servir de guide pour l’élaboration de plans de caractérisation de sites dans des environnements similaires affectés par le pergélisol et pour évaluer leur potentiel ...